Rock hyraxes (Procavia capensis) and their environments : δ13Ccollagen and δ15Ncollagen as environmental indicators - La Grange, Lesa (Department of Archaeology, 2016)
Rock hyraxes (Procavia capensis) are a common component of faunal assemblages at South African archaeological sites. Previous studies have focused on their remains as proxies for aspects of diet and mobility in prehistoric human populations. They have also been recognized as valuable palaeoenvironmental indicators due to the fact that their stratified communal middens record shifts in stable isotopes, palynology, and molecular biomarkers that appear to reflect environmental change. Previous studies conducted in east Africa have concluded that rock hyraxes are preferential grazers. There is comparatively little evidence, however, for the dietary preference of South African rock hyraxes, although it has been suggested that they consume more browse. This research aims to quantify the carbon isotopic ratios in their bone collagen to reconstruct diet.